2012
DOI: 10.4103/0259-1162.108305
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of i-gel supraglottic device with classic laryngeal mask airway in anesthetized paralyzed children undergoing elective surgery

Abstract: Context:The newest variation of the i-gel supraglottic airway is a pediatric version.Aims:This study was designed to investigate the usefulness of the size 2 i-gel compared with the classic laryngeal mask airway (cLMA) of the same size in anesthetized, paralyzed children.Settings and Design:A prospective, randomized, single-blinded study was conducted in tertiary care teaching hospital.Subject and Methods:Sixty ASA grade I–II patients undergoing lower abdominal, inguinal, and orthopedic surgery were included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Their results suggest the i-gel is rapidly inserted in both manikins and patients by an inexperienced person and compares favourably to other supraglottic airways available. 5 Successful insertion of PLMA and i-gel in the first attempt without statistically significant difference in insertion time was observed in study by Jeon et al 11 Similar finding of successful insertion in first attempt were also observed in studies done by Das et al and Chen et al 18,19 In our study mean pulse rates, systolic and diastolic blood pressure, SpO 2 and EtCO 2 at all points of time interval were comparable and there was no statistically significant difference between the two groups with p value >0.05. Similar findings were observed by Helmy et al, Das et al, Chauhan et al in their study comparing LMA and i gel.…”
Section: -13supporting
confidence: 73%
See 1 more Smart Citation
“…Their results suggest the i-gel is rapidly inserted in both manikins and patients by an inexperienced person and compares favourably to other supraglottic airways available. 5 Successful insertion of PLMA and i-gel in the first attempt without statistically significant difference in insertion time was observed in study by Jeon et al 11 Similar finding of successful insertion in first attempt were also observed in studies done by Das et al and Chen et al 18,19 In our study mean pulse rates, systolic and diastolic blood pressure, SpO 2 and EtCO 2 at all points of time interval were comparable and there was no statistically significant difference between the two groups with p value >0.05. Similar findings were observed by Helmy et al, Das et al, Chauhan et al in their study comparing LMA and i gel.…”
Section: -13supporting
confidence: 73%
“…9,12,16,17 Das et al had observed higher number of manipulations to insert LMA than i-gel. 18 In our study device was placed in first attempt in 88% patients of group i-gel compared to 64% of group LMA. In group LMA 12% patient required second attempt and 16% required third attempt.…”
Section: -13mentioning
confidence: 99%
“…In the studies by Goyal et al [6] and [10] Unclear Unclear High* Unclear Kus et al [11] Unclear Unclear High* Unclear Gasteiger et al [12] Low Unclear High* Low † Goyal et al [6] Low Unclear High* Unclear Fukuhara et al [13] Low Unclear High* Unclear Das et al [7] Low Unclear High* Unclear Das et al [8] Low Unclear High* Unclear Lee et al [22] Unclear Unclear High* Unclear Theiler et al [18] Low Low High* Low † Tokgoz et al [14] Low Unclear High* Unclear Lee et al [16] Unclear Unclear High* Unclear Kim et al [17] Low Low High* Unclear Mitra et al [15] Low Unclear High* Unclear *Not possible to blind researchers to airway device used. †Intention to treat analysis stated.…”
Section: Oropharyngeal Leak Pressurementioning
confidence: 99%
“…Das et al [7,8] the authors compared the i-gel with two other airway devices and the results have been separated for ease of comparison. Three randomised trials compared the i-gel with the LMA Supreme TM (Teleflex Medical) and included a total of 150 patients.…”
Section: Study Selection Bias Information Bias Measurement Errors Conmentioning
confidence: 99%
See 1 more Smart Citation